Hatching magic - Downer, Ann, 1960-; Rayyan, Omar (New York : Aladdin Paperbacks, 2004)
When a thirteenth-century wizard confronts twenty-first century Boston while seeking his pet dragon, he is followed by a rival wizard and a very unhappy demon, but eleven-year-old Theodora Oglethorpe may hold the secret to setting everything right.
6.2
3-6
Keywords: Wizards -- Fiction; Dragons -- Fiction; Time travel -- Fiction; Magic -- Fiction; Fathers and daughters -- Fiction; Nannies -- Fiction; Wizards -- Fiction; Dragons -- Fiction; Time travel -- Fiction; Magic -- Fiction; Father-daughter relationship -- Fiction; Nannies -- Fiction